A new set of tables for detecting thresholds of color sensitivity in children with acquired myopia (Ukrainian Journal of Ophthalmology, 2026)
Background. Color vision, like visual acuity, is a function of cone cells in the retina of the eye. Development and improvement of this function goes in parallel with central vision development. The main cause of impaired vision in children with acquired myopia, aside from high myopic refraction, is incomplete, in a certain degree, development of the visual system. It is difficult to diagnose this pathology. Detection of color thresholds is important for assessing the degree of incomplete development of the visual system as well as for differentiating it from congenital color vision defects.The purpose. To objectify the method and to shorten the time required for testing the thresholds of color vision using a proposed new set of tables. Material and Methods. Thirty-five patients, aged 5 to 12 years old, with moderate and high myopia of both eyes which averaged (5.6±SD2.0) D.  No changes were seen in the fundus of the eye.  All children were performed ophthalmic examination including visual acuity test, refractometry, and binocular function test. Color threshold were detected using the proposed set of tables (a utility model No 114858 from March, 27, 2017; Bul. No 6) and using the commonly-used Rabkin’s tables.Results. We received the mean values of threshold as follows: 4.7±0.57 c.u. to red color,  2.6±0.24 c.u. to yellow, 3.1±0.38 c.u. to green, and 5.1±0.50 c.u. to blue color using the Rabkin’s tables; 2.6±0.65 c.u. to red color: 3.2± 0.61 c.u. to yellow, 1.9± 0.46 c.u. to green,  and 2.3±0.81  c.u. to blue color using the proposed tables.Conclusions. The comparison of the two methods showed that the proposed set of tables for testing thresholds of color vision simplify the test performance and minimize the time required for its passing. Also, it gives more objective and more accurate assessment of color perception and can be used for young children.
Keywords: thresholds of color vision; acquired myopia; amblyopia with myopic refraction; color vision threshold test in children